Legal Response to Corporate Fraud in South Korea: A Case Study of the Samsung C&T and Cheil Industries Merger Scandal - Hyunwoo Jeong (Law and Economy, 2025)
This paper explores the legal and corporate governance issues surrounding the Samsung C&T and Cheil Industries merger scandal in South Korea. The merger, which aimed to consolidate control within Samsung Group, was marred by allegations of insider trading, market manipulation, and fraudulent practices that disproportionately benefited top executives and institutional investors. Using this case as a focal point, the paper analyzes South Korea’s corporate law, particularly its mechanisms for regulating mergers and acquisitions and combating financial misconduct. Through a comparative analysis of South Korean regulations and international standards, such as the U.S. Sarbanes-Oxley Act and EU Corporate Governance Codes, the paper evaluates the effectiveness of South Korea’s legal framework in addressing large-scale corporate fraud. The study highlights the gaps in corporate governance and legal enforcement, calling for stronger reforms to ensure transparency, accountability, and shareholder protection. The paper concludes by discussing the broader implications of the scandal for public trust in corporate governance and the future of South Korean economic regulation.